BIOREMEDIASI SEBAGAI ALTERNATIF PENGEMBALIAN FUNGSI TANAH YANG TERCEMAR MINYAK BUMI - Zafira, zana (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2021)
Oil contamination from field drilling waste is aserious environmental problem worldwide.These oil contaminants must be removed tomaintain biodiversity and ecological balance.Bioremediation is a soil cleaning technique thatutilizes the metabolic ability of microorganismsto degrade soil contaminants. The use of nativebacteria producing biosurfactants andutilization of hydrocarbons increases theeffectiveness of bioremediation by makinghydrocarbons bioavailable for degradation.Determination of bioremediation microorganisms affects the degradationprocess of petroleum. This is because eachmicroorganism requires a specific substrate toreduce all the components of petroleum in thesoil. A deeper approach is needed to obtain theeffectiveness of microorganisms, bothnonindigenous and indigenous microorganismsthat are applied by researchers in degradingpetroleum. However, not all available journalsummaries provide a detailed explanation ofthe method and effectiveness of microorganisms in the bioremediation method.In this review, we will provide severalmicroorganisms and methods used inbioremediation, including adsorptive bioremediation, biopile, in-situ bioremediation,landfarming, biostimulation, and composting inorder to find the most effective method in thepetroleum bioremediation process.